Is an unhealthy work environment in nursing home care for people with dementia associated with the prescription of psychotropic drugs and physical restraints?. (2nd February 2016) - Willemse, Bernadette M.; de Jonge, Jan; Smit, Dieneke; Dasselaar, Wouter; Depla, Marja F. I. A.; Pot, Anne Margriet
ABSTRACT: Background: Research showed that long-term care facilities differ widely in the use of psychotropic drugs and physical restraints. The aim of this study is to investigate whether characteristics of an unhealthy work environment in facilities for people with dementia are associated with more prescription of psychotropic drugs and physical restraints. Methods: Data were derived from the first wave (2008–2009) of a national monitoring study in the Netherlands. This paper used data on prescription of psychotropic drugs and physical restraints from 111 long-term care facilities, residing 4, 796 residents. Survey data of a sample of 996 staff and 1, 138 residents were considered. The number of residents with prescribed benzodiazepines and anti-psychotic drugs, and physical restraints were registered. Work environment was assessed using the Leiden Quality of Work Questionnaire (LQWQ). Results: Logistic regression analyses showed that more supervisor support was associated with less prescription of benzodiazepines. Coworker support was found to be related to less prescription of deep chairs. Job demands and decision authority were not found to be predictors of psychotropic drugs and physical restraints. Conclusions: Staff's job characteristics were scarcely related to the prescription of psychotropic drugs and physical restraints. This finding indicates that in facilities with an unhealthy work environment for nursing staff, one is not more likely to prescribe drugs or restraints. Further longitudinal research is needed with special attention for multidisciplinary decision making – especially role of physician, staff's knowledge, philosophy of care and institutional policy to gain further insight into factors influencing the use of psychotropic drugs and restraints.